PENGEMBANGAN SIMULATOR FETAL BERBASIS KONTROL SUARA UNTUK PENGUJIAN ALAT FETAL DOPPLER - Royan -; Kusnanto Mukti Wibowo; Abdul Latif; Farid Ishartomo; Danu Tirta Nadi; Arif Mulyanto; Isnaeni Rofiqoch (Jurnal Ilmiah Poli Rekayasa, 2025)
Fetal Doppler is a diagnostic tool to detect fetal heart rate in BPM (beats per minute). Like other medical devices, it must be calibrated periodically by a health facility testing center, as stated in the Regulation of the Minister of Health of Indonesia Number 54 of 2015 article 4 paragraph 1. Article 8 paragraph 1 explains that testing or calibration of medical devices is carried out periodically at least once a year. In addition, testing must be carried out after repairs to medical devices as stated in SNI IEC 62353 of 2014. In addition to testing and calibration, medical devices need to be maintained and tested for function. Therefore, a fetal doppler simulator is needed by medical device technicians to test the function of the fetal doppler. The innovation made on this device is that the simulator is connected to a smartphone with the aim of minimizing electronic components, eliminating settings with buttons and replacing them with Voice Control on the smartphone. This fetal doppler simulator is successfully designed well, it can simulate fetal heart rate from 60-240 BPM with error value of 0% at settings of 90,120,150,180, and 240 BPM. While at setting 60 BPM there is an error value of 1.6%. This simulator is suitable for use as a reference for fetal doppler function test because the error value is below the tolerance of ±5 for BPM on fetal Doppler.